2019
DOI: 10.1021/acs.orglett.9b02267
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Enantioselective Ring-Opening of Cyclic Diaryliodoniums and O-Alkylhydroxylamines

Abstract: A preparation of 2-hydroxyamino-2′-iodobiaryls via the Cu-catalyzed enantioselective ring-opening reaction of cyclic diaryliodonium salts with O-alkylhydroxylamines is reported. 3,5-Di(tert-butyl)phenyl bis(oxazoline) was found to be the optimal ligand, and up to 99% ee values were achieved. The use of CaO as the base dramatically improved the yields and inhibited the side reactions. Finally, synthetic applications of these hydroxylamines were briefly demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…The newly obtained results indicated that these cMAVIs were vulnerable to triethylamine. On the other hand, their instability to bases implied that they might be highly reactive even without a transition metal, which is unusual for traditional cDAIs ( Li et al., 2019 ; Wu and Yoshikai, 2015 ). It would be valuable if their reactivity could be tuned under refined conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The newly obtained results indicated that these cMAVIs were vulnerable to triethylamine. On the other hand, their instability to bases implied that they might be highly reactive even without a transition metal, which is unusual for traditional cDAIs ( Li et al., 2019 ; Wu and Yoshikai, 2015 ). It would be valuable if their reactivity could be tuned under refined conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, a different Cu I /BOX (BOX = bisoxazoline) complex was used as the catalyst. 22 Aiming to introduce new functionalities into this system, the same group reported a Cu-catalysed asymmetric thiolative ring opening reaction for the synthesis of atropisomeric 2-thio-2 0 -iodo-1,1 0 -biphenyl derivatives. 23 In this case, the use of potassium thiocarboxylates as nucleophiles and Cu(CH 3 CN) 4 PF 6 /PhBOX as the optimal catalytic system delivered the desired thioesters satisfactorily in terms of reactivity and enantioselectivity (Scheme 10D).…”
Section: Desymmetrization Of Biaryls Via Ring-opening Reactions ‡mentioning
confidence: 99%
“…reported copper‐catalyzed enantioselective ring‐opening of cyclic diaryliodoniums and O ‐alkylhydroxylamines (Scheme 41). The base CaO played an important role in preventing side reactions and reaction gave high yields and the ligand 3,5‐di( t butyl)phenyl bis(oxazoline) gave high stereoselectivity [50] …”
Section: Transformations Involving Hypervalent Iodine Reagents and 1s...mentioning
confidence: 99%
“…The base CaO played an important role in preventing side reactions and reaction gave high yields and the ligand 3,5-di( t butyl)phenyl bis(oxazoline) gave high stereoselectivity. [50] Scheme 39. Aminotrifluoromethylation of alkenes.…”
Section: Ring-opening Of Cyclic Diaryliodonium Salts and O-hydroxylam...mentioning
confidence: 99%